2023
DOI: 10.6007/ijarems/v12-i3/19077
|View full text |Cite
|
Sign up to set email alerts
|

The Conceptual Frameworks of Advertising Literacy: A Systematic Literature Review

Yujue Wang,
Neesa Ameera Mohamed Salim,
Shafilla Subri

Abstract: Advertising has become an integral part of people's daily lives, and advertising literacy is a vital life skill that everyone should acquire. Scholars have proposed several conceptual frameworks of advertising literacy for the study of consumers' advertising literacy. The purpose of this study is to sort out the major conceptual frameworks of advertising literacy, aalyze the links and differences between the conceptual frameworks, and explore the veins and roots, with viewpoints to provide a reference for rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…More hashtags usually bring more likes (Li et al 2021), a feature that we found to be very important in separating Macro and Mega influencers. Recent studies also showed that joining a trend bandwagon contributes to higher engagement (Su et al 2020;Wang et al 2023).…”
Section: Discussionmentioning
confidence: 96%
“…More hashtags usually bring more likes (Li et al 2021), a feature that we found to be very important in separating Macro and Mega influencers. Recent studies also showed that joining a trend bandwagon contributes to higher engagement (Su et al 2020;Wang et al 2023).…”
Section: Discussionmentioning
confidence: 96%